1990
DOI: 10.1063/1.103474
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic precipitates and the semi-insulating properties of GaAs buffer layers grown by low-temperature molecular beam epitaxy

Abstract: Arsenic precipitates have been observed in GaAs low-temperature buffer layers (LTBLs) used as "substrates" for normal molecular beam epitaxy growth. Transmission electron microscopy has shown the arsenic precipitates to be hexagonal phase single crystals. The precipitates are about 6±4 nm in diameter with a density on the order of 10 17 precipitates per cm). The semi-insulating properties of the LTBL can be explained in terms of these arsenic precipitates acting as "buried" Schottky barriers with overlapping s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
112
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 444 publications
(116 citation statements)
references
References 9 publications
3
112
0
1
Order By: Relevance
“…6 The alternative model assigns the properties of LT GaAs to the formation of As-clusters in a buried Schottkybarrier model. 7 Ultrashort carrier lifetimes are attributed to either trapping in point defects or in As clusters.…”
mentioning
confidence: 99%
“…6 The alternative model assigns the properties of LT GaAs to the formation of As-clusters in a buried Schottkybarrier model. 7 Ultrashort carrier lifetimes are attributed to either trapping in point defects or in As clusters.…”
mentioning
confidence: 99%
“…By annealing the LT-GaAs samples, the EL2-like As Ga antisite defects precipitate into As clusters. 12 To avoid As evaporation during annealing, the samples were placed face down on a GaAs substrate. One piece of sample C was annealed at 600°C using the same procedure.…”
mentioning
confidence: 99%
“…Numerous studies have demonstrated that as-grown LT-GaAs contains t> 1% excess arsenic, producing a large concentration of As antisite-related defects (101~-102° cm 3), and that it also has a = 0.1% larger lattice constant than its bulk GaAs substrate [15,16]. The as-grown phase of LT-GaAs is known to have relatively low resistivity and mobility, so that even though it possesses a fast carrier response, it is not an outstanding photoconductor.…”
Section: Ultrashort Carrier Lifetimementioning
confidence: 99%